2020
DOI: 10.3389/fimmu.2020.568931
|View full text |Cite
|
Sign up to set email alerts
|

The Extrinsic and Intrinsic Roles of PD-L1 and Its Receptor PD-1: Implications for Immunotherapy Treatment

Abstract: Programmed death-ligand 1 (PD-L1) is an immune checkpoint inhibitor that binds to its receptor PD-1 expressed by T cells and other immune cells to regulate immune responses; ultimately preventing exacerbated activation and autoimmunity. Many tumors exploit this mechanism by overexpressing PD-L1 which often correlates with poor prognosis. Some tumors have also recently been shown to express PD-1. On tumors, PD-L1 binding to PD-1 on immune cells promotes immune evasion and tumor progression, primarily by inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 209 publications
(138 reference statements)
3
135
0
Order By: Relevance
“…ICIs against the programmed death-1 (PD-1, CD279) and its ligand, is an important focus in cancer immunology and oncology with FDA approval for various types of cancer. Immunotherapies targeting PD-1/programmed death-ligand 1 (PD-L1) signaling have now become the first-line treatment for some cancers due to their promotion of anti-tumor immune responses in patients with advanced cancers[ 14 ].…”
Section: Programmed Death-1/programmed Death Ligand 1 Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…ICIs against the programmed death-1 (PD-1, CD279) and its ligand, is an important focus in cancer immunology and oncology with FDA approval for various types of cancer. Immunotherapies targeting PD-1/programmed death-ligand 1 (PD-L1) signaling have now become the first-line treatment for some cancers due to their promotion of anti-tumor immune responses in patients with advanced cancers[ 14 ].…”
Section: Programmed Death-1/programmed Death Ligand 1 Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…PD-L1 is a 40-kDa type I transmembrane protein, which is expressed in immune cells (ICs) such as T cells, B cells, NK cells, DCs, macrophages, and myeloid-derived suppressor cells. It is also expressed in non-IC types including epithelial, endothelial, and tumor cells[ 14 , 23 ].…”
Section: Programmed Death-1/programmed Death Ligand 1 Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…siRNA has emerged as a powerful approach for cancer immunotherapy [68]. siRNA can target different molecules, such as programmed cell death-1 (PD-1) and its ligand (PD-L1), as well as interleukin 10 receptor, STAT3, and transforming growth factor-β receptor, on the surface of immune cells and/or tumor cells, which participate actively in the process of immune activation, to lessen tumor evasion from the host's immune system and boost the immune response against tumors [69][70][71][72]. Consistently, myeloid-derived suppressor cells (MDSC) are recognized as imperative inhibitors of T-cell responses in numerous malignancies, including PCa.…”
Section: Improving Antitumoral Immune Response By Sirnamentioning
confidence: 99%
“…PDL1 is one of the most important biomarkers for the prognostic prediction of immunotherapy. 14 A study has shown that higher PDL1 expression predicts superior clinical outcome with P D1/ P DL 1 inhibitors. 15 Although patients with positive PDL1 expression can benefit from P D1/ P DL 1 inhibitors, the association between the prognosis of patientsadministered antiangiogenic targeted drugs and PDL1 expression status remains unknown.…”
Section: Introductionmentioning
confidence: 99%